Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan Media Audio Canva Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas IV di SD Negeri Percontohan Kabanjahe - Rasita Karina Br Manulang; Irsan Irsan; Halimatusakdiah Halimatusakdiah; Faisal Faisal; Imelda Free Unita Manurung (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The purpose of this study was to determine the effect of using the PBL learning model assisted by audio canva media on the results of the division of grade IV students of SD Negeri Percontohan Kabanjahe. This study uses a Nonequivalent Control Group Design. This research was conducted at SD Negeri Percontohan Kabanjahe, Kabanjahe District, Karo Regency, North Sumatra Province. The population in this study were all grade IV students of SD Negeri Percontohan Kabanjahe in the 2023/2024 academic year. Data collection techniques in this study used interviews, tests, and documentation. And the analysis technique of this study used normality, homogeneity and hypothesis tests. Based on the results of the study, the t-statistic value = 8.99 was obtained with a p-value (two-tail) = 6.84E-13. Because the p-value <0.05, the null hypothesis (H₀) is rejected, which means there is a significant difference between the experimental class and the control class. Overall, the results of this study indicate that the PBL model assisted by Canva media has a significant influence on learning outcomes in Traffic material in grade IV of SD Negeri Pecontohan Kabanjahe in the 2024/2025 academic year.